Surgical management of upper cervical esophagus stricture caused by ingestion of corrosive substances – a single-center experience - Mishra, Haris Chandra; Mohapatra, Jyotiranjan; Dash, Sashibhusan; Dash, Sanghamitra (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Corrosive strictures of the upper cervical esophagus and hypopharynx are hard to treat in the operating room because there is a high chance of aspiration during swallowing after a high-up or proximal esophageal anastomosis. In this cases, we aimed to evaluate the role of intraoperative dilatation of the proximal hypopharyngeal and cervical esophageal stumps during surgery. Material and methods. Patients who underwent surgery and had upper cervical esophageal and hypopharyngeal strictures from corrosive substance ingestion were included. Results. Out of total 27 patients, 10 had a cricopharyngeal or proximal cervical esophageal stricture with a long segment tho racic esophageal stricture that was treated with intra-operative dilatation (IOD) of the proximal hypopharyngeal stump. IOD was done in two cases with Hegar’s dilator and in three cases with wire-guided Savary Gillard dilators. In 74% (20/27) of the cases, the colon was frequently used as an esophageal substitute, while the stomach was only used in 10 cases. On follow-up, none of them developed repeated aspirations or required a tracheotomy. Conclusion. IOD of the proximal hypopharyngeal and cervical esophageal stumps during surgery for corrosive upper cervi cal esophageal or cricopharyngeal strictures helps to save the proximal stump and avoid frequent hospital stays and multiple surgeries.
All subjects gave their informed consent for inclusion before they participated in the study (001/NEW/EC/INST/2023/15947). The study was conducted in accordance with the Declaration of Helsinki.
Keywords: corrosive injury of the esophagus; dilatation; esophageal replacement surgery; esophageal stricture